Waste Management Policy In Tourism Area of Saensuk Municipality, Thailand - Pongsathon Kaewmanee; Andy Fefta Wijaya (Journal of Indonesian Tourism and Development Studies, 2014)
Saensuk Municipality is a famous tourism city in Thailand, especially Bangsaen beach. In supporting the tourism activity, it has waste managing method by using new generation administrator and technologies. However, the waste problem happened in Saensuk Municipality is included the human resource ability, technical facility, and the amount of waste. By using the qualitative descriptive method and doing a series of interview to selected informants, the researcher studied and analyzed the problem, factors, and solutions of the issue. This study found that the nature of the beach and the visitor behavior is among the reason behind the large amount of waste daily in the site. Moreover, the regulation by the local government is sufficient to cover the issue if implemented fully. The study shows that the city had implemented the good governance idea in several instances, and giving the waste management to the private sector is one of the optionsto resolve the problem since the quality of the work could be improved. Keywords:waste management,public policy, tourism area, Thailand